26 Digoxin – Friend or Foe? A Comprehensive Review of Digoxin use and Mortality - Ziff, Oliver; Kotecha, Dipak; Samra, Monica; Kirchhof, Paulus; Steeds, Richard; Griffith, Michael; Townend, Johnathan; Lip, Gregory YH (Heart (British Cardiac Society), 2015)
BackgroundDigoxin use in heart failure and atrial fibrillation are common but declining, and remain the subject of conflicting clinical viewpoints. Recent observational studies have suggested increased mortality in patients receiving digoxin. We sought to clarify the impact of digoxin on clinical events, accounting for study designs, methodology and potential bias, regardless of clinical indication.MethodsA comprehensive search of Medline, Embase and Cochrane from 1960 onwards identified 59 studies. 40 studies were suitable for meta-analysis with 67 study analyses comparing digoxin with either placebo or no treatment: 34 unadjusted, 19 adjusted, 10 propensity-matched and 4 randomised controlled trials (RCTs). All-cause mortality was meta-analysed using a random effects model according to study design and the review was prospectively registered (PROSPERO: CRD42014010783).Results467,273 patients were included for meta-analysis. Those treated with digoxin were 2.4 years older than control (weighted difference; 95% CI 1.3–3.5) with lower ejection fraction (33% vs. 42%) and more diabetes. Concomitant use of diuretics and anti-arrhythmic drugs (AAD) was also greater with digoxin therapy (see Table 1). Compared to control, the pooled risk ratio for death in digoxin-treated patients was 1.7 in unadjusted observational analysis (95% CI 1.5–2.0), 1.9 in adjusted observational analyses (95% CI 1.5–2.3), 1.1 in propensity-matched analyses (95% CI 1.0–1.4) and 1.0 in RCTs (95% CI 0.9–1.1); see Figure 1. Meta-regression of observational studies confirmed that differences between treatment arms had a significant impact on the risk associated with digoxin use, including diabetes (p = 0.01), diuretics (p = 0.001), and AAD (p = 0.01); see Figure 2.Abstract 26 Table 1Baseline characteristics – Digoxin versus controlBaseline characteristicWeighted mean difference/Odds ratio95% Confidence Intervalp-valueAge (years)WMD 2.401.29–3.50<0.001DiabetesOR 1.341.16–1.55<0.001Male genderOR 0.890.80–1.000.05DiureticOR 3.502.49–4.92<0.001Beta-blockerOR 0.750.62–0.920.004AADOR 1.721.14–2.600.009Abstract 26 Figure 1Summary meta-analysis of all-cause mortality with digoxin use according to study designAbstract 26 Figure 2Meta-regression plots of digoxin versus controlConclusionDigoxin is not associated with increased mortality in RCTs. The impact of digoxin on clinical outcomes should not be assessed in observational studies due to fundamental differences in patients receiving treatment. Future RCTs are crucial to accurately estimate the clinical value of digoxin therapy on clinical outcomes.